2014
DOI: 10.1007/s00408-014-9572-y
|View full text |Cite
|
Sign up to set email alerts
|

Progression and Prognostic Indicators of Bronchial Disease in Children with Sickle Cell Disease

Abstract: Purpose The pulmonary complications of sickle cell disease (SCD) are a leading cause of morbidity and mortality (MacLean et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…A similar prevalence was found in a retrospective cohort study conducted by Williams et al, 33 who demonstrated that 35.9% of the patients had a diagnosis of asthma and that a decline in FEV 1 as a percentage of predicted is associated with progression to pulmonary dysfunction. These findings underscore the need for the recognition of asthma, as well as the importance of longitudinal follow-up of pulmonary function, in this population.…”
Section: Discussionsupporting
confidence: 82%
“…A similar prevalence was found in a retrospective cohort study conducted by Williams et al, 33 who demonstrated that 35.9% of the patients had a diagnosis of asthma and that a decline in FEV 1 as a percentage of predicted is associated with progression to pulmonary dysfunction. These findings underscore the need for the recognition of asthma, as well as the importance of longitudinal follow-up of pulmonary function, in this population.…”
Section: Discussionsupporting
confidence: 82%
“…Treatments such as short-acting beta2 agonists and/or inhaled corticosteroids, are known to delay progression of pulmonary dysfunction (Williams et al, 2014). Treatments such as short-acting beta2 agonists and/or inhaled corticosteroids, are known to delay progression of pulmonary dysfunction (Williams et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors identified in our study could have possible implications for clinicians. Treatments such as short-acting beta2 agonists and/or inhaled corticosteroids, are known to delay progression of pulmonary dysfunction (Williams et al, 2014). In young children with SS homozygous or Sb 0 compound heterozygous SCD, the treatment of bronchial obstruction, or adenoidectomy and/or tonsillectomy could possibly modify the risk and course of CV.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also observed a history of asthma in one third of SCD patients, which is double the prevalence observed in the population of children and adolescents in the city of Belo Horizonte (17.8%), according to the International Study of Asthma and Allergies in Childhood . These findings underscore the need for the recognition of asthma, as well as the importance of longitudinal follow‐up of pulmonary function, in this population . This may also indicate that several inflammatory mechanisms are involved in the genesis of airway obstruction in SCD …”
Section: Discussionmentioning
confidence: 99%